Advances in serological diagnostics of inflammatory myopathies. Issue 5 (October 2016) - Benveniste, Olivier; Stenzel, Werner; Allenbach, Yves
Abstract : Purpose of review: Inflammatory myopathies are rare diseases. Their diagnosis criteria are historically based on their clinical phenotype (topography of the muscle weakness, presence of skin lesions and/or of extra-skin/muscle signs) and the presence of inflammatory infiltrates on muscle biopsy. However, the recent discovery of different myositis-specific antibodies (MSA) or myositis-associated antibodies (MAA) permitted to revisit these old classifications. This review covers recent findings in clinical and pathological phenotypes regarding prognosis, associated cancer and response to the treatment based on MSA/MAA categorization. Recent findings: Since the mid-1970s, about 20 MSA or MAA were discovered year after year (by immunoprecipitation). Now commercial kits (mainly dot line assays) permit their detection routinely which is clearly a help for the diagnosis but also give some key indications on clinical features, risk of associated cancers and response to the treatments. Summary: Overlap myositis is associated with antisynthetase antibodies (Abs) or those associated with sclerodermia (anti-RNP, Ku and PM-ScL). Dermatomyositis is associated with anti-Mi2, small ubiquitin-like modifier activating enzyme (SAE), nuclear matrix protein-2 (NXP2), TIF-1γ or melanoma differentiation-associated gene 5 (MDA5) Abs. Immune-mediated necrotizing myopathies are associated with anti-signal recognition particle (SRP) or 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR) Abs. One third of inclusion body myositis' patients also presented anti-cytosolic 5′-nucleotidase 1A (cN1A) Abs. The risk of associated cancers is elevated with anti-TIF-1γ, NXP2 or HMGCR Abs.